Promotion of Lotus tenuis and calf early weaning as a good management practice for breeding herds in marginal soils of the Flooding Pampa (Argentina) - Bailleres, Matías Andres (2020)
The promotion of forage legumes in marginal environments for agriculture constitutes a major technological challenge for livestock farming. The legume Lotus tenuis .Waldst. & Kit.) is a good example of beneficial naturalization in the Salado River Basin, that is, in the largest area dedicated to bovine farming in the country. The aim of this study was to evaluate the promotion of L. tenuis in marginal areas as a valuable alternative for early weaning systems in livestock production. Two treatments were tested during three study periods. To evaluate the efficiency of the proposed system, average daily weight gain (DWG) and weight gain (WG) of conventional weaning (CW) and early weaning (EW) calves were determined and compared. EW calves grazing on L. tenuis gained more weight than CW calves during Study period 1 (P = 0.028), but no differences were observed between treatments during Study periods 2 and 3 (P ˃ 0.05). Body Condition Score (BCS) for dams in both treatments was evaluated. For all three study periods, BCS improvement was higher in cows from the EW treatment than in Lactating cows (LC) from the CW treatment. Thus, EW improved cow BCS and did not generate weight reductions in calves thanks to the Lotus-based diet. In conclusion, L. tenuis promotion in the summer season resulted higher yields in marginal areas than semi–natural pastures. It also provided an acceptable nutritional value to properly fed a considerable amount of calves on a small surface area, and enabled a better recovery of the dams in terms of body condition. The obtained results support the design of an easy-to-use strategy that facilitates adoption by producers.